Current status of evaluation and treatment of early-stage remnant gastric cancer - Huang, Yinghui; Ma, Li; Ren, Keyu; Gao, Qun; Zhu, Zhenming; Wang, Guangrong; Cao, Bin (Frontiers in Oncology, 2024)
Because of early diagnosis and improved prognosis, patients with gastric cancer are now surviving longer and remnant gastric cancer after gastrectomy is becoming more common. Remnant gastric cancer is traditionally considered a malignancy with a dismal outcome. However, recent advances in diagnostic and therapeutic strategies have improved outcomes. In recent years, the development of endoscopic therapy has provided us with new therapeutic ideas. Although with some drawbacks, such as limited working space, gastric fibrosis and staples under the suture line, endoscopic management is still an effective treatment option with potential long-term survival advantage. For gastrectomy patients, endoscopic surveillance should also be recommended, for prompt surveillance and detection in the early remnant gastric cancer. This review aims to provide an overview of remnant gastric cancer, especially focusing on its pathogenesis as well as new advances in the diagnosis and endoscopic treatment of early-stage remnant gastric cancer.